AB0467 Efficacy and safety of assisted reproductive technologies (ART) in rheumatic patients: a multicenter study. (15th June 2017) - Reggia, R; Sebbar, H; Andreoli, L; Hoxha, A; Larosa, M; Ceccarelli, F; Canti, V; Ramoni, V; Inversetti, A; Ruffatti, A; Doria, A; Conti, F; et al.
Abstract : Background: Always more frequently rheumatic patients (pts) ask for Assisted Reproductive Technologies (ART) for infertility problems. The main concern is determined by the ovarian stimulation, associated with an increased risk of disease flare and thrombosis. Objectives: To describe a case series of ART cycles in pts affected by rheumatic diseases, analyzing pregnacy rate and outcome, fetal-maternal complications and disease flares. Methods: We included all the consecutive pts evaluated in the Pregnancy Clinic of 5 Italian Rheumatology Units after having performed ≥1 ART cycle from 1997 to 2016. Results: We included 60 pts: infertility was primary (no previous spontaneous conception) in 68% of cases, idiopathic in 76.5%, of male origin in 8.3%, of female origin in 15%, mixed in 0.2%. One hundred and eleven ART cycles were performed: 13IUI, 44FIVET (3eterologous), 53ICSI (14eterologous), 1embryodonation. Antiphospholipid antibodies were positive in 23 (38.3%) pts and in 45 (40.5%) cycles. Procedures were unstimulated in 14 (12.6%) stimulated in 97 (59.5%) cases: with GnRH-Antagonist in 26 (26.8%), GnRH-agonist in 60 (61.8%), gonadotropins only in 7 (7.3%) and with clomiphene in 4 (4.1%) cases. We registered 3 (3%) cases of Ovarian Hyperstimulation Syndrome, all after Agonist protocol. Overall we observed 46 pregnancies, with a pregnancy rate of 38.7% for omologous procedures and of 55.5% for eterologous. No miscarriages were reported. Pregnancies ended with 35 single and 5 twin birth, 6 are still ongoing: we recorded 4 (8.9%) perinatal deaths: 1 baby died at birth for multiple malformations and 3 died in the first days of life for extreme prematurity. One or more fetal complications were reported in 11 (27.5%) pregnancies: 3PROM, 3IUGR, 3oligohydramnios, 4fetal malformation (2 severe, 1multiple and fatal). The mean age of the women suffering from fetal complications was significantly lower (p:0.03). One or more maternal complications were reported in 13 (32.5%) pregnancies: 4gestational diabetis, 2thrombocytopenia, 2pre-eclampsia, 2placenta previa, 1hypothyroidism, 1gestational hypertension, 1cholestasis of pregnancy. Disease Flares were reported in 5 (12.5%) pregnancies: 4 articular (2 in RA patients, 2 in SLE patients), 1haematological (in SLE patient, after spontaneous therapy discontinuation). No cases of thrombosis were reported.During puerperium: 1 (2.5%) post-partum hemorrage (no LMWH ongoing), 1 articular flare (2.5%). Additional informations are available in Table 1 . Conclusions: We didn't found any good reasons to discourage ART performance in rheumatic pts: the safety seems to be high and the complications rate is in line with that reported in general population. An adequate prophylaxis during stimulation, pregnancy and puerperium seems to provide a good protection from thrombotic complications. Disclosure of Interest: None declared